Summary of food safety planning workshop for three Local governments in Ibadan, Nigeria - International Institute of Tropical Agriculture; Akinyele L.G.; Ibadan N.L.G.; Ibadan S.E.L.G. (International Institute of Tropical Agriculture, 2025)
IITA, Akinyele LG, Ibadan North LG and Ibadan South East LG, Summary of Food Safety Planning Workshop for Three Local Governments in Ibadan, Nigeria, IITA, Ibadan, Nigeria, May 2025, pp 1-9 On the 18th and 19th of February 2025, Food Safety for Africa (FS4Africa) project team of the International Institute of Tropical Agriculture (IITA) led by Dr. Titilayo Falade, hosted a planning workshop at IITA. The goal of the planning workshop was to interact with representatives the local governments and consultatively identify the food safety challenges and chart a plan of action for advancing food safety within the informal sector in the local government. Mrs. Olumodupe Banwo, Programs Manager, IITA Capacity Development Office and Project Manager, FS4Africa moderated the workshop.